2011
DOI: 10.1590/s1413-81232011000500014
|View full text |Cite
|
Sign up to set email alerts
|

Contracepção hormonal: uma comparação entre pacientes das redes pública e privada de saúde

Abstract: O objetivo deste artigo é avaliar o perfil de pacientes usuárias de contraceptivos hormonais no setor público e fazer a comparação com o serviço privado de saúde, bem como verificar a frequência de efeitos colaterais e a aderência ao tratamento. Realizou-se um estudo de corte transversal com 240 pacientes, sendo 120 da rede privada e 120 da rede pública de saúde. No grupo privado, a dosagem hormonal mais frequentemente prescrita foi a de 15 ou 20 microgramas de etinil-estradiol (EE), associados a gestodeno, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
1
0
9
Order By: Relevance
“…Of these, the majority was aged between 17 and 34 years, which corroborates other studies that also showed a predominance of young women in current or past use of contraceptive methods [11][12]. This finding may be justified by the wide dissemination of knowledge regarding hormonal contraceptives, especially among young people.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of these, the majority was aged between 17 and 34 years, which corroborates other studies that also showed a predominance of young women in current or past use of contraceptive methods [11][12]. This finding may be justified by the wide dissemination of knowledge regarding hormonal contraceptives, especially among young people.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the importance of investigating such a background is assessed as predictive factor for the actual use of the contraceptive, directing health professionals, women and/or couples in this choice. The analysis of this variable is considered essential for clinical evaluation, given that it allows the identification of risk factors for onset of other diseases associated with the use of hormonal contraceptive, such as metabolic, cardiac and cerebrovascular diseases and cancer, among others [12,[18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Conforme apontaram alguns dos estudos, uma das principais causas para a interrupção dos métodos contraceptivos pelas mulheres foi justamente a existência de efeitos colaterais associados ao uso (PRADO; SANTOS, 2011;BAHAMONDES et al, 2011;GOMES et al, 2011;MONTEIRO, 2015).…”
Section: Planejamento Reprodutivo Nounclassified
“…-Cefaleia (BAHAMONDES et al, 2011;GOMES et al, 2011;CARDOSO et al, 2019;BRAGA;VIEIRA, 2015;PANISSET;GIORDANO;GIORDANO, 2015;MORAES et al, 2015);…”
Section: Planejamento Reprodutivo Nounclassified
“…Em outro estudo realizado com 240 pacientes, sendo 120 da rede privada e 120 da pública, os autores mostraram que a estenilestradiol (EE), foi o hormônio mais prescrito (48,3%) em ambas a redes, não havendo diferença entre a frequência dos efeitos colaterais. Nos seus resultados, também pode-se perceber que o grupo privado tem maior aderência e cuidado ao uso e tratamento, e que esse resultado pode estar associado ao fator sociocultural dessas pacientes (2,12) . Ressalta-se, que no Brasil a utilização do ACHO vem aumentando desde 2006.…”
Section: Discussão O Uso De Anticoncepcionais Orais: Aspectos Clínicos E Teóricosunclassified